Counter-Hegemonic Discourse on the Experience of Disability: Retrieving the Voices of Female Students with Disabilities Who are Involved in the Juvenile Justice System - Matsuda, Kazuko (2007)
This study challenged the traditional conception of disability as an individual problem and problematized the invisibility of young females with disabilities in the juvenile justice system in educational research. The purpose of this study was to contextualize the experience of disability and its intersectionality with race, gender, and social class. In doing so, the study aimed to elucidate a range of challenges that young females with disabilities must handle in and outside schools. The selected method was a qualitative mode of inquiry. The participants were comprised of ten females between 12 and 17 years of age. Multiple methodologies were utilized to give participants voices, prioritize their perspectives, and make their everyday struggles visible in educational scholarship. The study demonstrated that the experience of disability is a complex social phenomenon. It was revealed that the deep-seated cultural assumptions and images of disability permeated school practices and continued to subjugate young females with disabilities. When disability intersected with race, gender, and social class, the overlapping effects of multiple marginalities produced greater barriers for young females with multiple margins to obtaining equal educational opportunities. This study recognized the need to redefine disability in order to transform educational practices and empower young females at multiple margins